Development and evaluation of the Basic Outcome Measure Protocol for Aphasia (BOMPA). (4th May 2021) - Kagan, Aura; Simmons-Mackie, Nina; Shumway, Elyse; Victor, J. Charles; Chan, Lisa
Abstract: Purpose: The Basic Outcome Measure Protocol for Aphasia (BOMPA) is a practical tool that allows for a quick self-report on quality of life from the perspective of the person with aphasia, as well as a clinical evaluation of aphasia severity and the ability to participate in conversation. The primary aim of this paper is to describe development of BOMPA and report on results of an inter-rater reliability study involving speech-language pathology raters. Method: The inter-rater reliability study utilised a fully crossed design and included independent ratings of 12 videos by 20 speech-language pathologists. Result: Results indicate moderate to strong inter-rater reliability among participant speech-language pathology raters (0.65–0.96), as well as when comparing these participant ratings with an expert rater's gold standard (0.59–0.86). Conclusion: BOMPA may be a useful outcome measurement tool for time-pressed clinicians in clinical settings.